Formation of New Territories in Residents’ House in Tourism Kampung - Vincentia Aprilia Devi Ratnasari; Happy Ratna Sumartinah; Dewi Septtanti (Institut Teknologi Sepuluh Nopember, 2020)
Changing an ordinary kampung into a tourist kampung will provide changes in every aspect of the kampung. These changes are among the changes in terms of social, economic, cultural, environmental, and activities in the tourist kampung. Through the change of activities automatically forms a new regulatory system in its spatial and function. then comes the urge of citizens to maintain and form a private territory to other activities (tourist activities). so it needs to know how the villagers form their new territory in the outer space of their dwelling to get the comfort and privacy that suits their needs. The method used to determine the formation of new territories carried out by citizens using studies from research that raised similar phenomena that have occurred. After that, a comparison is made with field data or the current conditions of the current tourist kampung. The results obtained will find the form of citizens' efforts to form new territories with their boundaries. The boundaries are adjusted to the factors that shape it such as space requirements, spatial functions, activities, and the perpetrators of these activities. Then it can be used to indicate other changes that occur in the tourist kampung.